Distributed Ledger Technologies, Value Accounting, and the Self Sovereign Identity - Manski, Sarah (Frontiers in Blockchain, 2020)
Technological activists are designing blockchains and other distributed ledger technologies to challenge extractive value-accounting and identity management in global capitalism. This paper investigates how the new possibilities afforded through distributed ledger technology make possible an alternative future of generative value accounting and self-sovereign identity practices.